(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
An important role in maintaining homeostasis at all levels, i.e., from cells to the whole organism, is assigned to the microhemocirculation system, which combines the microcirculatory system and the rheological properties of the blood. Disruption of microcirculation has a significant impact on the development of pathological processes. The microcirculation system responds early, uniformly and generally to the occurrence of pathological changes in one of its regions. The study of microcirculation also makes it possible to indirectly judge the state of the mechanisms that ensure the regulation of the functional state of microvessels (Petrov V.V., Moldavskaya A.A., Levitan B.N., Khrappo N.S. Hemomicrocirculatory bed and blood rheology in traumatic nosebleeds / / Modern high-tech technologies. – 2005. – No. 4. – P. 29-32; Popelnyuk N.S., Davydkin I.L., Kozlova O.S., Krivova S.P., Kuzmina T.P., Naumova K.V. The problem of studying the processes of microcirculation and blood rheology in the clinic of internal diseases (literature review doi.2S694/U RW .2019.08.2). One of the most important links in the pathogenesis of purulent-inflammatory diseases of the paranasal sinuses are changes in microhemocirculation (Fokkens WJ, Lund VJ, Hopkins C., Hellings PW, Kern R., Reitsma S., et al. European Position Paper on Rhinosinusitis and Nasal Polyps 2020 Rhinology 2020 Suppl. 29: 1-464).